2011
DOI: 10.1590/s0074-02762011000200009
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive ecology of bat flies (Diptera: Hippoboscoidea) associated with vampire bats (Chiroptera: Phyllostomidae) in the cerrado of Central Brazil

Abstract: We studied the ectoparasitic bat flies of three phyllostomid vampire bat species. Bats were collected monthly from April 2004-March 2005 True ectoparasites spend most of their adult lives, or all developmental phases, on the bodies of their hosts or in their hosts' shelters (Marshall 1982). Streblidae (Diptera: Hippoboscoidea) are obligate ectoparasites of bats (Dick & Patterson 2008) and, consequently, are found primarily in tropical areas with relatively few species in the subtropical and warm temperate zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 28 publications
1
17
0
2
Order By: Relevance
“…S. curvata, recorded as monoxenous, was usually found on bats of the genus Glossophaga (Wenzel 1976, Dick & Gettinger 2005), but we collected this species on a specimen of Carollia brevicauda (Schinz). S. wiedemanni Kolenati was found parasitising several species of bats (Marinkelle & Grose 1981, Guerrero 1996b, Graciolli & Carvalho 2001, Rios et al 2008, Rojas et al 2008), but we only found it on Desmodus rotundus (É. Geoffroy St.-Hilaire) (monoxenous), which is considered its primary host (Aguiar & Antonini 2011). Noctiliostrebla aitkeni Wenzel is known mainly as a parasite of Noctilio leporinus (Linnaeus) and recorded as monoxenous, but we found this species in sympatry with P. fusca on one specimen of N. leporinus (MMD 2809), an association also observed by Graciolli and Carvalho (2001).…”
Section: Resultsmentioning
confidence: 58%
“…S. curvata, recorded as monoxenous, was usually found on bats of the genus Glossophaga (Wenzel 1976, Dick & Gettinger 2005), but we collected this species on a specimen of Carollia brevicauda (Schinz). S. wiedemanni Kolenati was found parasitising several species of bats (Marinkelle & Grose 1981, Guerrero 1996b, Graciolli & Carvalho 2001, Rios et al 2008, Rojas et al 2008), but we only found it on Desmodus rotundus (É. Geoffroy St.-Hilaire) (monoxenous), which is considered its primary host (Aguiar & Antonini 2011). Noctiliostrebla aitkeni Wenzel is known mainly as a parasite of Noctilio leporinus (Linnaeus) and recorded as monoxenous, but we found this species in sympatry with P. fusca on one specimen of N. leporinus (MMD 2809), an association also observed by Graciolli and Carvalho (2001).…”
Section: Resultsmentioning
confidence: 58%
“…In addition to the new records of associations (Table I), we found the following variations in the component communities: the absence of Paraeuctenodes similis Wenzel, 1976 on C. perspicillata, association observed in regions of Atlantic forest (Bertola et al in 2005, Prevedello et al 2005 and Amazon forest (Guerrero 1996); the absence of Metelasmus pseudopterus Coquillet, 1907, which is found parasitizing species of Artibeus from the south-central Brazil (Eriksson et al 2011, Bertola et al 2005; the lower number of ectoparasitic species on Desmodus rotundus (E. Geoffroy, 1810), that in other areas of cerrado is also parasitised by Trichobius furmani Wenzel, 1966 and Strebla wiedemanni Kolenati, 1856 (Eriksson et al in 2011, Aguiar andAntonini 2011); the absence of Trichobius uniformis Curran, 1935 andStrebla curvata Wenzel, 1976 on Glossophaga soricina (Pallas, 1766), found on this species in cerrado areas (Eriksson et al 2011, in addition to the parasitism by Paraeuctenodes longipes Pessoa et Guimaraes, 1937 recorded in the southern Brazil (Graciolli and Rui 2001). It is also highlighted the absence of parasitism on A. cinereus, a species with register of parasitism by ectoparasitic flies of the genus Neotrichobius Wenzel and Aitken, 1966 in the Amazon region (Guerrero 1994a).…”
Section: Discussionmentioning
confidence: 98%
“…In the neotropics, bat species harboring more than one fly species has been observed also in areas of tropical forest (Teixeira andFerreira 2010, Bertola et al 2005), cerrado (Aguiar and Antonini 2011), Venezuela (Wenzel 1976) and eastern Amazon forest . In this study, the highest proportion of hosts with infracommunities of ectoparasitic flies (40.5%) was found mainly in Lophostoma species (Table II).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pela facilidade de captura e de manipulação do hospedeiro e a melhor visualização dos dípteros sobre o corpo de morcegos, vários artigos têm sido publicados sobre a ocorrência de dípteros ectoparasitos de morcegos no Brasil (por exemplo, Dias et al, 2009;Graciolli & Bianconi, 2007;Graciolli et al, 2010;Lourenço & Esbérard, 2011;Aguiar & Antonini, 2011). Além disso, artigos recentes sobre a taxonomia dessas famílias de dípteros ectoparasitos de morcegos têm facilitado a identificação dos gêneros e das espécies e despertado o interesse de estudantes e pesquisadores (Dick & Miller, 2010;Graciolli, 2004;Graciolli & Azevedo, 2011;Graciolli & Carvalho, 2001a;2001b;Graciolli & Dick, 2012;Graciolli & Moura, 2005), enquanto importantes contribuições sobre a taxonomia de hipoboscídeos neotropicais são mais escassos (Graciolli & Carvalho, 2003;, sendo os mais importantes publicados a mais 40 anos (Bequaert, 1954;Maa, 1969;Peterson & Maa, 1970), por exemplo.…”
Section: Lipoptena Mazamae (Rondani 1878) Ozotocerosunclassified